Makna Multimodal Pada Buku Tematik Kelas III SD - Wulansari, Fitri; Wulan, Adistia Primi (CAKRAWALA LINGUISTA, 2024)
This study aims to analyze the form of modality contained in class III thematic books. The method used in this study is the elucidating strategy. The form of research used is subjective with a balanced approach. The source of information used in this exam was Topical textbooks for class III SD-MI with a book size of 29.7 cm and 70 gr HVS paper type. Multicolor book tone with an extraordinary limitation technique, brand with a replacement book model and distributed by the Instruction office in 2018. The instrument used in this study was to use multimodal content analysis study tables in student books which contain themes, sub-themes, learning, pages titles, forms of activities/pages (images) that contain multimodal using table analysis of ideational, interpersonal, and textual meaning intersemiosis. Checking the information used by this researcher is content investigation. The results of the data analysis that the researcher did, from the three Thematic Learning books for class III SD, not all of them contain a multimodal form. Researchers only found 26 data from the three thematic books. In the three themes the researcher found verbal multimodal forms and nonverbal multimodal forms. Of the 26 data, 11 data contained verbal multimodal forms and 15 data contained non-verbal multimodal forms.